2016
DOI: 10.1073/pnas.1613316113
|View full text |Cite
|
Sign up to set email alerts
|

Permissive roles of cytokines interleukin-7 and Flt3 ligand in mouse B-cell lineage commitment

Abstract: Hematopoietic cells are continuously generated throughout life from hematopoietic stem cells, thus making hematopoiesis a favorable system to study developmental cell lineage commitment. The main factors incorporating environmental signals to developing hematopoietic cells are cytokines, which regulate commitment of hematopoietic progenitors to the different blood lineages by acting either in an instructive or a permissive manner. Fms-like tyrosine kinase-3 (Flt3) ligand (FL) and Interleukin-7 (IL-7) are cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…SiglecH is a specific marker for plasmacytoid dendritic cells (pDC), which also express B220 (Blasius et al , ; Zhang et al , ). Previously, it was shown that SiglecH was also expressed by a fraction of CLP and pre‐pro‐B cells (Medina et al , ), two populations partially overlapping with EPLM (von Muenchow et al , ). Since pDC also express the general dendritic cell marker CD11c (Singh‐Jasuja et al , ), we chose this as a third surface marker.…”
Section: Resultsmentioning
confidence: 99%
“…SiglecH is a specific marker for plasmacytoid dendritic cells (pDC), which also express B220 (Blasius et al , ; Zhang et al , ). Previously, it was shown that SiglecH was also expressed by a fraction of CLP and pre‐pro‐B cells (Medina et al , ), two populations partially overlapping with EPLM (von Muenchow et al , ). Since pDC also express the general dendritic cell marker CD11c (Singh‐Jasuja et al , ), we chose this as a third surface marker.…”
Section: Resultsmentioning
confidence: 99%
“…One difficulty with compartmentalizing cells in this manner is a lack of knowledge about the functions of some of these surface molecules during developmental progression. For example, the cellular functions of CD34, CD48 and CD150, and of markers such as Ly6D and SiglecH that are used to subdivide HPC in the case of early progenitors with lymphoid and myeloid potential (EPLM), are not known …”
Section: Hematopoietic Stem Cells and Various Progenitors Are Heterogmentioning
confidence: 99%
“…For instance, Fms‐like tyrosine kinase‐3 ligand and Interleukin‐7—cytokines deemed pivotal for B‐cell development, as manifested by the severely compromised B‐cell development in their absence—were finally shown to be dispensable. [ 61 ]…”
Section: Constraints Drive Cell Fate Commitment Toward a Finite Numbementioning
confidence: 99%
“…For instance, Fms-like tyrosine kinase-3 ligand and Interleukin-7-cytokines deemed pivotal for B-cell development, as manifested by the severely compromised B-cell development in their absence-were finally shown to be dispensable. [61] It is likely that the opposition in between the two hypothesis is far too simple a viewpoint of decision-making by the hematological tissue. [62] Putting emphasis on the role of the permissive factors (constraints and topological features of the landscape) is not to deny a function for specialized molecular actors (cytokines), which can reinforce cell fate commitment by amplifying signal-to-noise ratio once a specific trajectory has been selected.…”
Section: Constraints Drive Cell Fate Commitment Toward a Finite Numbementioning
confidence: 99%